2022
DOI: 10.1155/2022/4007048
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and Achievement Motivation among Iranian Nursing Students: A Descriptive Correlational Study

Abstract: Background. Happiness and achievement motivation are two important concepts in students’ lives. Therefore, this study was aimed at investigating the association between happiness and achievement motivation in undergraduate nursing students and examining their relationship with students’ demographic characteristics. Method. A descriptive correlational study was undertaken; 255 undergraduate nursing students enrolled in one nursing school in an urban area of Iran during the academic year 2017-2018 were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…Care and compassion are prerequisites for nursing practice [ 7 , 18 ]. Nurses play a central role in delivering holistic patient care by addressing the patient’s physical, psychological, social, and spiritual needs, enabling them to deal with their illness, restore their balance, and improve their lives [ 8 , 23 ]. Thus, the nursing practice is centered around caring and the caring behavior of nurses, which has a definite impact on the quality of patient care and patient satisfaction [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care and compassion are prerequisites for nursing practice [ 7 , 18 ]. Nurses play a central role in delivering holistic patient care by addressing the patient’s physical, psychological, social, and spiritual needs, enabling them to deal with their illness, restore their balance, and improve their lives [ 8 , 23 ]. Thus, the nursing practice is centered around caring and the caring behavior of nurses, which has a definite impact on the quality of patient care and patient satisfaction [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown relationships between happiness and depression, self-esteem, and interpersonal relationships among nursing students, which all may be associated with caring behaviors. Happiness is a subjective experience and a stable emotional state characterized by pleasant feelings and gratification, a sense of overall wellbeing, joy, prosperity, and personal growth [ 8 , 9 ]. Happiness is linked to reduced stress levels, increased resilience, greater self-confidence, and positive emotions and attitudes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the interviews, most of the students on urban campuses mentioned that “the subway is convenient in Shanghai,” whereas most of the students on suburban campuses complained that “there is no subway station and the bus is so slow and always late.” These findings suggest that low transportation accessibility puts suburban university students at a disadvantage when they apply for jobs after graduation. Additionally, perceived lower transit accessibility is related to lower happiness (Gim, 2020), which may be harmful to students' achievement motivations (Amani Nezhad et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that low transportation accessibility puts suburban university students at a disadvantage when they apply for jobs after graduation. Additionally, perceived lower transit accessibility is related to lower happiness (Gim, 2020), which may be harmful to students' achievement motivations (Amani Nezhad et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Gelecek durumla ilgili olumsuz tahminler, kötü senaryo oluşturma, olumsuza odaklanma ya da kötümser düşünme çıkmazı, hiçbir aktivite, önlem ya da davranış geliştirmeden kişiyi yorabilir. Hemşirelik öğrencileriyle yürütülen bir çalışmada mutluluk ile başarı motivasyonu arasında doğrudan anlamlı bir ilişki olduğu gösterilmiştir (18). Bazen bu kavram kişilerin duygusal zeka becerileri ile ilişkilendirilmektedir.…”
Section: Profesyonel Hemşi̇reli̇k Bakimi Kazaniminda Moti̇vasyonel Gö...unclassified